The Eating Inventory, body adiposity and prevalence of diseases in a quota sample of Czech adults - Hainer, V; Kunesova, M; Bellisle, F; Parizkova, J; Braunerova, R; Wagenknecht, M; Lajka, J; Hill, M; Stunkard, A (International journal of obesity (2005), 2006)
OBJECTIVE: To study the relationships between the Eating Inventory (EI) factors (restraint, disinhibition and hunger), body adiposity and prevalence of selected diseases in a quota sample of Czech adults. SUBJECTS AND METHODS: The sample included 1429 men and 1624 women who were interviewed individually by trained investigators. The sample was quota representative--for gender, age, size of residential location, region and socioeconomic status in Czech adults. Anthropometric data, socioeconomic and lifestyle information were obtained. Subjects filled out the EI questionnaire. Physicians reported about subjects' morbidity. RESULTS: Backward stepwise regression analysis revealed that restraint and disinhibition were significant predictors of body mass index (BMI) along with gender, age, parental obesity, weight loss attempts, present dieting and educational level. The same factors plus income predicted the waist circumference. BMI and waist circumference were negatively related to restraint but positively to disinhibition. According to logistic regression analysis restraint and disinhibition were significantly associated with hypertension, cardiovascular diseases and hyperlipidaemia. Diabetes was significantly related to restraint and hunger scores. The observed association between EI factors and diseases remained significant even when BMI and age were taken into account. CONCLUSION: As shown in earlier studies, disinhibition was positively and restraint negatively associated with BMI and waist circumference. For the first time, factors of the EI were also identified as significant predictors of diseases characterizing the metabolic syndrome.
Keywords: Logistic Models; diabetes mellitus; Diabetes Mellitus; stravovací zvyklosti; hyperlipidemie; Male; hypertenze; Obesity; Česká republika; Inhibition, Psychological; obezita; prevalence; Adult; dospělí; Motivation; mužské pohlaví; metabolický syndrom; Hypertension; průzkumy a dotazníky; logistické modely; Metabolic Syndrome; Czech Republic; lidé; Hyperlipidemias; motivace; ženské pohlaví; Humans; Body Mass Index; složení těla; Prevalence; Body Composition; index tělesné hmotnosti; inhibice (psychologie); Female; Surveys and Questionnaires; lidé středního věku; Middle Aged; Feeding Behavior